Lay leadership development in select Catholic schools - Manalang, Emmanuelle C. (College of Education, University of the Philippines Diliman, 2019)
Catholic education has contributed a lot in education for the past decades in terms of development of leadership theories and concepts, of educating a substantial number of students and of building a moral society. In the era of lay principalship in Catholic schools, transition of leadership from religious educators to lay educators have called for new approaches in formation and mentorship. The question of sustainability for Catholic schools stems from its unique identity and mission as an educational institution. This is developed among Catholic educators through the Christian Formation Program that Catholic schools implement. The CFP are designed to immerse the probationary teachers to the rigors, details and meaning of Catholic identity and missions. The CFP are conducted also to shape and form the integral person of the Catholic educator. Incidentally, CFP also help in the development of moral leadership of Catholic educators. Secondly, the faith of the Catholic educator is manifested in the performance of his/her responsibilities in the school. The spiritual capital of Catholic educators gives them the power to give witness to the person of Jesus to their students. The Catholic educator is also invited to partake with the Church in the work of evangelization, the task of telling and re-telling the story of Jesus. In the long run, the building of the spiritual capital of Catholic educators help develop their faith leadership at different levels and different areas. Lastly, mentoring a lay school principal entails both formal and informal support that are relevant to the needs and realities of the school. However, it was made clear that while these mentoring strategies are helpful, they are not sufficient to fully prepare the lay school principak for the leadership task. The person of the lay school principal plays the most vital role in leadership development. The mentorship program for lay school principal, therefore, should also incorporate the development of his/her integral person so that his/her faith will shape the development of his/her instruction and organizational leadership.